Impact of Biological Sex on Immune Activation and Frequency of the Latent HIV Reservoir During Suppressive Antiretroviral Therapy. (4th June 2020) - Falcinelli, Shane D; Shook-Sa, Bonnie E; Dewey, Morgan G; Sridhar, Sumati; Read, Jenna; Kirchherr, Jennifer; James, Katherine S; Allard, Brigitte; Ghofrani, Simon; Stuelke, Erin; Baker, Caroline; Roan, Nadia R; et al.
Abstract: Background: Persistent HIV infection of long-lived resting CD4 T cells, despite antiretroviral therapy (ART), remains a barrier to HIV cure. Women have a more robust type 1 interferon response during HIV infection relative to men, contributing to lower initial plasma viremia. As lower viremia during acute infection is associated with reduced frequency of latent HIV infection, we hypothesized that women on ART would have a lower frequency of latent HIV compared to men. Methods: ART-suppressed, HIV seropositive women (n = 22) were matched 1:1 to 22 of 39 ART-suppressed men. We also compared the 22 women to all 39 men, adjusting for age and race as covariates. We measured the frequency of latent HIV using the quantitative viral outgrowth assay, the intact proviral DNA assay, and total HIV gag DNA. We also performed activation/exhaustion immunophenotyping on peripheral blood mononuclear cells and quantified interferon-stimulated gene (ISG) expression in CD4 T cells. Results: We did not observe evident sex differences in the frequency of persistent HIV in resting CD4 T cells. Immunophenotyping and CD4 T-cell ISG expression analysis revealed marginal differences across the sexes. Conclusions: Differences in HIV reservoir frequency and immune activation appear to be small across sexes during long-term suppressive therapy. Abstract : Cross-sectional analysis of age- and race-matched antiretroviral-suppressed HIV seropositive participants demonstrated no evident sex differences in the frequency of inducible replication-competent HIV or intact HIV DNA within resting CD4 T cells. Marginal sex differences in immune activation markers were observed.